Belemnite ecology and the environment of the Nusplingen Plattenkalk (Late Jurassic, southern Germany): evidence from stable isotope data. (7th July 2014) - Stevens, Kevin; Mutterlose, Jörg; Schweigert, Günter
<x xml:space="preserve">Abstract</x> The late Kimmeridgian Nusplingen Plattenkalk (palaeolatitude 30°N) is one of the well‐known European Plattenkalk konservatlagerstätten. The laminated limestones of this lagerstätte have been deposited in a shallow lagoon, surrounded by sponge‐microbial mounds, some of which formed small islands. Plattenkalk sediments are often thought to have been deposited below a halocline, which was induced by high evaporation rates. By measuring the stable isotope composition of belemnite rostra (n = 27) of the species Hibolithes semisulcatus, the depositional environment of the Nusplingen Plattenkalk has been investigated. Cathodoluminescence‐microscopy and trace element analysis have been applied to check for diagenetic alteration of the studied rostra. The mean δ13C of the well‐preserved rostra is +0.03 ± 0.27‰, the mean δ18O −0.68 ± 0.3‰. A narrow range of stable isotope data acquired from an accumulation of rostra, regurgitated by a fish or reptile, supports the notion that belemnite calcite reflects environmental conditions. The palaeontological and sedimentological findings suggest that H. semisulcatus was autochthonous to the Nusplingen Plattenkalk. Anoxic conditions prevailed in the sediments and temporarily in the water‐column above the sediment/bottom water interface. A nektobenthic life style can be excluded for the Nusplingen belemnites; a demersal life style seems unlikely. Comparison with δ18Obel data from other latitudes indicates that a latitudinal gradient played a role in the δ18O composition of seawater. A pelagic, inner shelf setting is therefore suggested for the Plattenkalk, an interpretation that is supported by palaeontological evidence. It is here proposed that the formation of the Nusplingen Plattenkalk was not caused by salinity stratification. It is further suggested that the belemnites were not restricted to deep‐water settings, but also occurred in shallow waters and higher in the water‐column.